Effects of Atorvastatin on Atherosclerosis and Atherogenesis in Systemic Lupus Erythematosus: A Pilot Study. (19th March 2014) - Sokoll, Katharina Benita; Batuca, Joana; Lopez, Luis Romulo; Hensor, Elizabeth; Emery, Paul; Delgado Alves, José; Ames, Paul Richard Julian
Abstract : Objective . The effect of statins on atherogenesis in systemic lupus erythematosus (SLE) is poorly known. To inform a wider trial we performed a pilot study evaluating the intima-media thickness of the common carotid artery (CIMT) and some oxidative [beta-2-glycoprotein-1 complexed with oxidised low density lipoprotein (β 2 GPIoxLDL)], metabolic [paraoxonase (PON), nitrate (NO 3   − ), nitrite (NO 2   − ) and nitrotyrosine (NT)], inflammatory [C-reactive protein (CRP) and serum amyloid A (SAA)], and lipid markers before and after 1 year of treatment with 40 mg of oral atorvastatin (AT). Methods . Randomised, double blind, placebo controlled pilot study on consecutive SLE patients: 17 SLE patients were randomised into the AT arm and 20 into the placebo arm. CIMT was measured by high-resolution sonography, PONa by a spectrophotometric method, NO 3   − and NO 2   − by a colorimetric assay and oxLDL-β 2 GPI, NT, CRP, and SAA by Elisa. Results . After correction for age and disease duration oxLDL-β 2 GPI decreased by 27% (P = 0.002 ) and PON/HDL ratio increased by 12% (P = 0.01 ) but CIMT did not change. Conclusion . This pilot study revealed a decrease of oxLDL-β 2 GPI (oxidant marker) and an increase of PON/HDL ratio (antioxidant activity) after AT indicating a favourable effect of the drug on atherogenic pathways that should be explored on larger trials.